Comparing Husbands' Addiction in Women With and Without Exposure to Domestic Violence - Mona Rahnavardi; Mahboubeh Ahmadi Dolabi; Mehrzad Kiani; Asma Pur Hoseyn Gholi; Arezoo Shayan (Guilan University of Medical Sciences, 2018)
Introduction: Domestic violence is considered a serious threat to the health and rights of women throughout the world. Evidence indicates that addiction and the consumption of narcotics and alcohol is among important individual causes resulting in violence against women. Objective: This research aimed to compare the impact of the addiction of the spouses on women who were subject of violence with women who were not subject of violence. Materials and Methods: This was an analytical cross-sectional study. The study samples included 110 women referring to health and treatment centers and the family courts of the city of Rasht, Iran selected by the convenience sampling method. Study tools included the World Health Organization questionnaire on domestic violence. The questionnaire s reliability was assessed through intraclass reliability coefficient. Descriptive statistics indicators and Independent t test, Chi-square test, Mann Whitney test, and the repeated measures ANOVA were used for data analysis. Results: The mean age of the participants in the non-violated group and in the violated group were (32.69±7.65) and (33.94±6.92) years, respectively. The most rated violence was psychological violence with 44.13%, followed by the physical violence with 33.88% and the sexual violence with 30.9% in the group who have experienced domestic violence. The use of opium (P=0.03), and heroin (P=0.002) was significantly higher in the spouses of women who had experienced domestic violence compared to the spouses of women without experiencing domestic violence. However, no significant difference was seen between the two groups, with regard to smoking and the use of psychedelic drugs and consumption of alcohol. Conclusion: Considering the high incidence of domestic violence against women who participated in this research and recognizing that addiction is a major risk factor in violence against women, psychological health policies should consider preventive plans and allocate resources to prevent violence against women and its terrible consequences.